Using TikTok as a platform for science communication: the latest challenges and opportunities (PUBMET, 2022)
The pandemic has changed the way we interact. The popularity of the TikTok platform, which allows creating short video content, was on the rise even before 2020 and skyrocketed during quarantine. Scientists have recognized its potential as a new means to communicate and share experience.This poster will take a look at the content posted by the most popular science communicators and at the reasons for creating content of this type.As the hashtags on the platform can be used to categorize content for algorithms and AI to understand it, we will explore science-related hashtags using information available at https://tiktokhashtags.com/ and select the most popular profiles (personal TikTok profiles of science communicators) for analysis in terms of science content, differences between video creators and presenters, and their background. The background will be analyzed from content posted on the platform (if they are openly talking about it on the platform) and comparison with content posted on other platforms. We will also look for reasons for their switching to TikTok. Our hypothesis is that shifts in social dynamics in the wake of coronavirus pandemic favoured a switch from big productions to user-friendly platforms like TikTok, and that its video-making options encourage those less experienced in video-making to create and share (science-related) content.As TikTok is an open platform with egalitarian public engagement model, it can be used to build trust in science by, say, showing the process “behind the scenes”.
Keywords: open science communication; science communication; social media hashtags; TikTok